2020
DOI: 10.1128/aem.00893-20
|View full text |Cite|
|
Sign up to set email alerts
|

Alterocin, an Antibiofilm Protein Secreted by Pseudoalteromonas sp. Strain 3J6

Abstract: The aim was to identify and study the antibiofilm protein secreted by the marine bacterium Pseudoalteromonas sp. 3J6. The latter is active against marine and terrestrial bacteria, including Pseudomonas aeruginosa clinical strains forming different biofilm types. Several amino acid sequences were obtained from the partially purified antibiofilm protein, named alterocin. The Pseudoalteromonas sp. 3J6 genome was sequenced and a candidate alt gene was identified by comparing the genome-encoded proteins to the sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The extract could have been adsorbed on some places of the surface, explaining the holes, or released during the biofilm formation phase, or it could have modified the biology or chemistry of the cell, leading to long-term effects that could have reduced biofilm production or a caused a decrease in its stability. Dheilly et al [ 14 ] observed similar results with alterocin, an antibiofilm protein which reduced biofilm formation of P. aeruginosa when applied during the attachment step only [ 28 ].…”
Section: Resultsmentioning
confidence: 88%
“…The extract could have been adsorbed on some places of the surface, explaining the holes, or released during the biofilm formation phase, or it could have modified the biology or chemistry of the cell, leading to long-term effects that could have reduced biofilm production or a caused a decrease in its stability. Dheilly et al [ 14 ] observed similar results with alterocin, an antibiofilm protein which reduced biofilm formation of P. aeruginosa when applied during the attachment step only [ 28 ].…”
Section: Resultsmentioning
confidence: 88%
“…An alternative hypothesis is that the architecture of the biofilm, rather than the organization of the ami operon, may explain the strain specific differences in OSTN susceptibility. Indeed, characterization of the clinical strains selected in the panel demonstrated that they form biofilms with significant differences in biofilm spatial organization and matrix composition [ 50 , 71 ]. Moreover, it was recently observed that P. aeruginosa PA14 exposed to hANP modifies the exopolysaccharides composition of the biofilm matrix [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, the genome sequence of P. piscicida strain DE2-B by Richard et al [ 110 ] revealed relatively the same genes responsible for the production of antimicrobial proteolytic enzymes and compounding, including peptides, polyketides, and alkaloids; thus, the P. piscicida strain DE2-B’s ability to inhibit some bacteria, including, V. parahaemolyticus . Jouault et al [ 111 ] sequenced Pseudalteromonas sp. 3J6 and identified gene sequences, including the alt gene, which encodes 139 residue proteins and is responsible for the expression of alterocin, a protein implicated in inhibiting P. aeruginosa biofilms.…”
Section: Pseudoalteromonas Spp; Therapeutic Potentials and S...mentioning
confidence: 99%
“…Studies in aquaculture have identified diverse marine bacterial species as potent probiotics [ 111 , 112 , 113 ]. Some identified bacteria can be considered safe (GRAS) for humans, while others are pathogenic.…”
Section: Limitations Prospects Future Perspectivesmentioning
confidence: 99%